Contested relationships: Women's economic and social empowerment, insights from the transfer of material assets in Bangladesh - Lucy Scott (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This article examines the relationship between women's economic and social empowerment in the context of extreme poverty. It is based on the findings of primary fieldwork on the char islands of north-west Bangladesh, investigating the processes resulting from the implementation of the Chars Livelihoods Programme (CLP). The first phase of the CLP, funded by the UK government's Department for International Development (DFID), operated from 2004-2010. Its central activity was the transfer of approximately 100s' worth of investment capital to targeted extremely poor households. This investment capital was given specifically to a woman within that household and the majority of these female beneficiaries used it to purchase cattle. This article argues that interventions which adopt primarily an economic entry point can contribute to women's empowerment beyond the economic realm, including in terms of changing intra-household relationships and increasing women's self-esteem. Clearly interventions beyond the economic sphere are needed to ensure that this empowerment is sustainable and can contribute to changing social norms. However, the contribution which practical gender needs make in providing a basis for extremely poor women to achieve their future strategic gender needs should not be underestimated.
Keywords: F35; I32; J12; J16; 330; extreme poverty; asset transfer; female empowerment; Bangladesh; Armut; Weibliche Arbeitskräfte; Bangladesch